Neural Blockade in the Evaluation and Management of Chronic Pain: An Overview - Ian Gilron (Pain Research and Management)
Local anesthetic and neurolytic nerve blocks have been used for over a century in the evaluation and management of chronic pain, despite a the dearth of evidence supporting their application. This article provides a general overview of the physiology and pharmacology of nerve blocks and suggests how they may affect pathophysiological mechanisms of chronic pain. Following a discussion of the rationale, clinical application and potential complications of nerve blocks, existing evidence of efficacy is reviewed. Further research evaluating mechanisms and efficacy of nerve blocks is vital to define their role in chronic pain management.